(untitled) (Eurasian Scientific Herald, 2024)
This article aims to explore practical ideas and strategies for sustaining motivation in the process of learning foreign languages. Language learning motivation plays a crucial role in learners’ progress and overall success. However, sustaining motivation can be challenging, particularly in long-term language learning endeavors. This article reviews current research literature and provides practical recommendations to help learners maintain their motivation throughout their language-learning journey. The strategies discussed encompass goal setting, relevance, enjoyment, study routines, varied learning resources, community engagement, progress tracking, embracing mistakes, rewards, and maintaining a positive mindset. By implementing these practical ideas, language learners can enhance their motivation levels and effectively sustain their language learning momentum